Single Nucleotide Polymorphism Analysis of the Follicle-stimulating Hormone (FSH) Receptor in Japanese with Male Infertility : Identification of Codon Combination with Heterozygous Variations of the Two Discrete FSH Receptor Gene - Shimoda, Chiharu; Koh, Eitetsu; Yamamoto, Kenrou; Matsui, Futoshi; Sugimoto, Kazuhiro; Sin, Ho-Su; Maeda, Yuji; Kanaya, Jiro; Yoshida, Atsumi; Namiki, Mikio (Endocrine journal, 2009)
Dysfunction of the FSH receptor (FSHR) may be involved in some form of male infertility with azoospermia or oligozoospermia. We assessed the discrete codon combination with homo/heterozygous variation of the exon 10 in the FSHR gene. The genotype of codon 307 and codon 680 were analysed in 352 patients with idiopathic male infertility and 145 men with proven fertility. There was no significant difference in the distributions of each homozygous codon 307 or 680 between these two groups as reported in the literature. However, the population with heterozygous combinations Thr/Ala (codon 307) and Ser/ Asn (codon 680) comprised 26% (38/146) and 44.9% (157/343) in subjects with proven fertility and idiopathic infertile men, respectively. Moreover, the heterozygous genotype Thr/Ala-Ser/Asn was significantly increased in infertile patients compared with the controls. This finding showed that the combination of heterozygous FSHR can be responsible for male infertility.